2019
DOI: 10.1111/flan.12377
|View full text |Cite
|
Sign up to set email alerts
|

When a heritage speaker wants to be a Spanish teacher: Educational experiences and challenges

Abstract: This study explored the experiences of eight Latina heritage speakers (HSs) who were enrolled in world language teacher preparation programs at two higher education institutions. Using data from interviews, classroom observations, and other documents, the qualitative multiple‐case study investigated their educational experiences and the challenges involved in attaining initial Spanish teacher certification. Four themes emerged: motivation to become a world language teacher, language awareness, developing profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The absence of critical discussions on raciolinguistic power hierarchies within the educational experiences of these groups did not inhibit their ability to recognize these dynamics, it simply reinforced that the classroom was not a place to disrupt such sociopolitical realities. Bustamante and Novella (2019) confirm these findings in their qualitative multiple-case study wherein Latina heritage language PSTs had their linguistic practices devalued as not standard or grammatical enough for their WL pedagogy courses. The Black American participants from Anya's 2016 study depended on the nonclassroom community as a preferred context for Portuguese languaging in the absence of discussing sociopolitical realities within the classroom.…”
Section: Literature Reviewsupporting
confidence: 61%
See 2 more Smart Citations
“…The absence of critical discussions on raciolinguistic power hierarchies within the educational experiences of these groups did not inhibit their ability to recognize these dynamics, it simply reinforced that the classroom was not a place to disrupt such sociopolitical realities. Bustamante and Novella (2019) confirm these findings in their qualitative multiple-case study wherein Latina heritage language PSTs had their linguistic practices devalued as not standard or grammatical enough for their WL pedagogy courses. The Black American participants from Anya's 2016 study depended on the nonclassroom community as a preferred context for Portuguese languaging in the absence of discussing sociopolitical realities within the classroom.…”
Section: Literature Reviewsupporting
confidence: 61%
“…The Black American participants from Anya's 2016 study depended on the nonclassroom community as a preferred context for Portuguese languaging in the absence of discussing sociopolitical realities within the classroom. Still, while the Latina PSTs from Bustamante and Novella's (2019) study used their language skills in the community, they later found said skills were not valued in their university-based courses, as they were not considered academic enough. Similarly, raciolinguistic ideologies were either transferred, as with Bacon's (2020) mixed-methods study with 127 novice teachers, or endured through societal norms, as with Dobbs & Leider's (2021) qualitative study with fifteen novice and early career teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding highlights the lack of representation of heritage speakers in the SHL teacher pool, which may impact students' motivation, engagement, and achievement (Egalite et al, 2015;González Darriba et al, 2021;Guzman, 2020). Early engagement programs dedicated to fostering interest in language teaching among SHL speakers at the high school level could result in a relevant shift, with larger number of SHL learners becoming the future practitioners in the field, thus serving the trifold purpose of helping them and their students to maintain, value, and expand their use of the language (Bustamante & Novella, 2019;Guzman, 2020). (b) Stand-alone professional development options.…”
Section: Discussionmentioning
confidence: 99%